2015
DOI: 10.1371/journal.pone.0134951
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Really Know about Cognitive Inhibition? Task Demands and Inhibitory Effects across a Range of Memory and Behavioural Tasks

Abstract: Our study explores inhibitory control across a range of widely recognised memory and behavioural tasks. Eighty-seven never-depressed participants completed a series of tasks designed to measure inhibitory control in memory and behaviour. Specifically, a variant of the selective retrieval-practice and the Think/No-Think tasks were employed as measures of memory inhibition. The Stroop-Colour Naming and the Go/No-Go tasks were used as measures of behavioural inhibition. Participants completed all 4 tasks. Task pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 92 publications
2
38
2
Order By: Relevance
“…It is important to mention that non-dysphoric participants also failed to show a forgetting effect in the unaided suppression condition. This is contrary to previous research which has demonstrated successful a successful suppression-induced forgetting effect (Anderson and Green, 2001;Joormann et al, 2009;Noreen and MacLeod, 2015). Our findings are, however, consistent with a growing body research that has failed to demonstrate below-baseline forgetting using the TNT task (Bulevich, Roediger, Balota and Butler, 2006;Nørby, Lange and Larsen, 2010;Hertel and Gerstle, 2003).…”
Section: Discussioncontrasting
confidence: 85%
“…It is important to mention that non-dysphoric participants also failed to show a forgetting effect in the unaided suppression condition. This is contrary to previous research which has demonstrated successful a successful suppression-induced forgetting effect (Anderson and Green, 2001;Joormann et al, 2009;Noreen and MacLeod, 2015). Our findings are, however, consistent with a growing body research that has failed to demonstrate below-baseline forgetting using the TNT task (Bulevich, Roediger, Balota and Butler, 2006;Nørby, Lange and Larsen, 2010;Hertel and Gerstle, 2003).…”
Section: Discussioncontrasting
confidence: 85%
“…The inhibitory deficit hypothesis of aging suggests that many age-related cognitive and social deficits depend on poor inhibitory control [42, 43]. Although this hypothesis and the underlying construct validity of inhibition in older adults are still issues of debate [44, 45], our results suggest that at least the ability to inhibit mental routines worsens in older adults, unless its deterioration is actively counteracted by designed, physical-cognitive DT training. This finding extends and further specifies the notion that physical activity training has the potential to induce cognitive plasticity in older adulthood [11], thus preserving the efficiency of supervisory brain systems in which inhibition is involved [46].…”
Section: Discussionmentioning
confidence: 68%
“…While aerobic exercise is the most acknowledged form of exercise to reap cognitive benefits through cardiovascular and neurotrophic mechanisms inducing changes in brain health and activation, more recently, other types of exercise besides the cardiovascular one have attracted the attention of exercise and cognition researchers [10]. Muscular resistance training of yearly [45] or even monthly duration [50] seems to improve inhibition by enhancing functional plasticity of the cortex associated with inhibition processes [51]. This was observed, for example, with women aged 65 to 75 years by means of high intensity resistance training, even only once a week, of major muscle groups (arms flexions and extensions, seated row, upper limbs pull downs, leg press, legs flexions, and raises on ball of the foot), paralleled by specific strategies to promote participants' engagement [52].…”
Section: Discussionmentioning
confidence: 99%
“…Noreen and MacLeod () showed no commonalities or correlations between tasks such as Stroop, think/no‐think, go/no‐go, and memory retrieval tasks, suggesting that these paradigms primarily assess different aspects of inhibitory processes and that there is more than one mechanism underlying behavioral inhibition (Noreen and MacLeod, ). Stahl et al () used a multi‐component modeling approach and suggested separability of cognitive inhibition (termed “stimulus interference” in their study) from response interference, which tend to be undifferentiated in existing studies (Noreen and MacLeod, ). Stahl et al () also suggested that the control of response‐related interference itself is not a unitary construct.…”
Section: Introductionmentioning
confidence: 99%